Analysis of the structure and factors determining the economic parameters of multiproject interaction in the construction industry - POLZIKOV, Myroslav (Ways to Improve Construction Efficiency, 2025)
Multiproject interaction in the construction industry reflects a complex system of economic, financial, organizational, and temporal interconnections between projects within a unified portfolio. It forms a specific type of economic architecture in which the performance of each project is determined not in isolation, but through a network of mutual influences. The key factors defining the economic parameters of such a system include resource interdependence, joint financing, regulatory constraints, technological overlaps, and temporal correlations in project execution. Each of these factors manifests through synergistic or conflict effects that shape the dynamics of an enterprise’s financial stability. Effective management of multiproject interaction requires the application of a factor – structural approach that enables the quantitative description of nonlinear interactions among portfolio elements. The proposed model of integral efficiency E(t) treats financial outcomes as a function not only of individual project profitability but also of interdependence coefficients δᵢⱼ(t), which measure the strength of cross-influences between projects. This approach allows identifying both synergy effects (shared resource use, procurement optimization) and cannibalization effects (internal competition, resource overload). Of particular importance are cross-financial loadings that arise from fund transfers between projects to maintain liquidity. They play a dual role – providing short-term portfolio stabilization while simultaneously creating risks of long-term instability through depletion of internal reserves. The mathematical function of financial tension Fₙᵗ(t) reflects the dynamics of these processes, accounting for time lags, compensatory flows, and the degree of mutual financial dependency among projects. Factor–structural analysis in multiproject systems serves as a key forecasting tool. It enables the identification of nodal portfolio elements where risks concentrate and the determination of critical points of destabilization. Its application lays the foundation for developing digital twins of construction enterprises and implementing analytical monitoring systems that ensure proactive risk management. Consequently, multiproject interaction is viewed not as a set of isolated processes but as a unified dynamic economic system whose efficiency depends on the coherence, adaptability, and resilience of its internal interconnections.